2018
DOI: 10.1111/cbdd.13316
|View full text |Cite
|
Sign up to set email alerts
|

Development of coumarin–benzofuran hybrids as versatile multitargeted compounds for the treatment of Alzheimer’s Disease

Abstract: Alzheimer's disease (AD), the most common cause of dementia, is a neurodegenerative disorder characterized by progressive deterioration of memory and cognition. The evidenced multifactorial nature of AD has been considered the main reason for the absence of cure so far. Therefore, the development of novel hybrids to treat the disease is very much essential. Focusing on this, a novel series of coumarin-benzofuran hybrids have been designed and screened as anti-Alzheimer's disease agents. The strategy is to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…6,7 Moreover, benzofuran derivatives are also biodynamic agents that can be used to design and develop new potential therapeutic agents. 8 In recent years, researchers have found that such compounds have various biological activities including: anti-tumor, 9 antibacterial, 10,11 anti-oxidative, 1,12,13 anti-AD, 14 anti-parasitic, 15 anti-acetylcholine, 16 and anti-inammatory activities. 17 They can also be used as bone anabolic agent, 18 and uorescent sensor for analgesic 19 The most well-known and recognized natural products containing benzofuran ring structure, include ailanthoidol, amiodarone and bufuralol compounds.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Moreover, benzofuran derivatives are also biodynamic agents that can be used to design and develop new potential therapeutic agents. 8 In recent years, researchers have found that such compounds have various biological activities including: anti-tumor, 9 antibacterial, 10,11 anti-oxidative, 1,12,13 anti-AD, 14 anti-parasitic, 15 anti-acetylcholine, 16 and anti-inammatory activities. 17 They can also be used as bone anabolic agent, 18 and uorescent sensor for analgesic 19 The most well-known and recognized natural products containing benzofuran ring structure, include ailanthoidol, amiodarone and bufuralol compounds.…”
Section: Introductionmentioning
confidence: 99%
“…, 2005; Al-Bassam et al. , 2010; Aher and Akhmanova, 2018; Hiremathad et al. , 2018; Lindeboom et al.…”
Section: Introductionmentioning
confidence: 99%
“…In the second model, changes in the structure and/or the activity of the depolymerizing microtubule end disrupt depolymerization and promote polymerization. This model is primarily supported by previous studies of proteins that selectively bind to microtubule ends and promote rescue, including CLASP, CLIP--170, and Kip3/kinesin 8 16,17,[19][20][21][22][23][24] . It is unclear whether this is also a property of tubulin alone.…”
Section: Introductionmentioning
confidence: 76%
“…Instead, rescue may disrupt the depolymerizing end structure. Several conditions have been shown to promote rescue, including mechanical stress on the microtubule 15 , structural defects in the lattice 12 , slowing GTP hydrolysis 11 , and extrinsic regulation by microtubule--binding proteins 9,[16][17][18][19][20][21] . Nevertheless, we lack a basic understanding of the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%